Procrastination and self-regulation of learning in university students: a thematic essay (Research, Society and Development, 2022)
During academic life, it is necessary to create strategies for good performance in studies, but issues such as procrastination could make this fact difficult. Thus, the objective of this work was to discuss the postponement act in university students and the role of self-regulation of learning as a possible mediating variable, based on Albert Bandura's Social Cognitive Theory.  The methodology used was based on a bibliographic review of the narrative review type. The article is divided into 4 sections: introduction, methodology, results and discussion. In the introduction, the reasons for carrying out this work were presented; in the results are highlighted the general aspects of the Theory studied, the self-regulation of learning and procrastination in higher education, this observed with its possible relationships to the construct of Bandura's Theory through time management and environmental and cognitive factors; finally, some conclusions were discussed by the authors. The main results show the need for awareness of procrastination as a problem, the demand for creating ways to face it, such as self-regulation of learning and the lack of dissemination of the theme through greater textual production.